The use of serum extracellular vesicles for novel small molecule inhibitor cell delivery. Issue 3 (March 2019) - Hatzidaki, Eleana; Vlachou, Ioanna; Elka, Aspasia; Georgiou, Evanthia; Papadimitriou, Maria; Iliopoulos, Aggelos; Papasotiriou, Ioannis
Abstract : In Research Genetic Cancer Center (RGCC), we are in the process of synthesizing a novel ERK inhibitor. We have currently synthesized an intermediate molecule, RGCC169, that needed to be tested to confirm we are using the appropriate synthetic pathways. Because of the limited solubility the compound exhibits, a strategy had to be devised for the free entrance of the molecule into the cell. Extracellular vesicles (EVs) were isolated by polyethylene glycol precipitation and identified by western blot and scanning electron microscopy. Loading was determined by high-performance liquid chromatography, differential scanning calorimetry, and scanning electron microscopy. EV uptake was determined by fluorescent microscopy. The effect of EV-encapsulated RGCC169 was determined by MTT viability assay on MCF7 cells. RGCC169 was incorporated into EVs as shown by high-performance liquid chromatography (26.6%) and scanning electron microscopy. Differential scanning calorimetry peaks shifted from 100.84 to 108.79°C upon encapsulation. EVs were taken up by cells as evident from CD63 fluorescent signal inside the cell's cytoplasm. RGCC169 decreased MCF proliferation (93.5±2.2, P= 0.02). EV-encapsulated RGCC169 decreased cell proliferation even further (93.5±2.2 vs. 81.6±2.8, P =0.0002). RGCC169 was successfully loaded into serum EVs possibly by incorporation into the lipid membrane. EVs were taken up by MCF7 cells possibly by endocytic pathways. Although RGCC169 significantly reduced MCF7 viability at 3 μmol/l, the same concentration of RGCC169 encapsulated into EVs decreased cells viability even further. Our findings validate the correctness of our methods and are very promising for the achievement of our final goal, that is, the synthesis of a novel cytotoxic agent.